Spatial variation in host-parasite interactions in the three-spined stickleback - de Roij, Job (2011)
The role of parasites as agents of selection on their hosts has been well established, but less is known about how parasites facilitate divergence among host populations. In this thesis, I used the three-spined stickleback, Gasterosteus aculeatus, as a model organism to explore spatial variation in host-parasite interactions and the consequences for divergence of host traits. First, I established the extent of spatial variation in natural infection in the study system, North Uist, Outer Hebrides, Scotland, by conducting a survey of macroparasite communities in twelve freshwater lochs over two years. I found substantial geographic variation in parasite communities that was remarkably stable in time. Assuming that differences in parasite community composition correspond to differences in parasite-mediated selection, it suggests that North Uist stickleback populations experience divergent parasite-mediated selection that is consistent in time. Next, I carried out a series of artificial infection experiments with lab-reared sticklebacks from five populations using three widespread macroparasite species (Gyrodactylus gasterostei, Diplostomum spathaceum and Schistocephalus solidus), to assess geographic variation in parasite resistance and a component of the innate immune system, the respiratory burst response. There was significant variation among populations in resistance to G. gasterostei and D. spathaceum, and the innate immune response. To some extent the variation was related to natural infection levels, suggesting that divergent parasite-mediated selection may drive investment in these traits. Lastly, I conducted a growth experiment with the five stickleback populations and showed that there was significant population-level variation in juvenile growth rate, an important life history trait. In spite of considerable variation in all traits, I found no evidence for genetic trade-offs across populations between juvenile growth rate, and macroparasite resistance or the innate immune response. This thesis adds to a growing body of work that emphasises the importance of space in shaping host-parasite interactions.